Normative community pressure in brand community: a study of young entrepreneurs community of mandiri bank - Lindiawati Lindiawati; Indrianawati Usman; Sri Wahyuni Astuti (Journal of Economics, Business, and Accountancy Ventura, 2019)
Brand community has been extensively built and developed by either the companies or the customers voluntarily. These two gorups with different perspective hold different purposes. For the companies, brand community is considered an effective marketing strategy which is expected to achieve customer brand engagement. Anyhow, often companies focus more on the purposes of the brand community, but do not be quite aware of the policies, rules, or traditions firstly created as norms in order to lead the way the community members perceive and act. Often norms become pressures for the brand community members causing them reluctant to engage with he community. Referring to the theory of relationship marketing, this study develops a model of normative community pressure that is affected by both brand community identification and inter-member relationship quality, that are previously affected by brand relationship quality. The empirical analysis derives primary data of young entrepreneurship community created by one of the big five banks in Indonesia quantitatively analyzed using Structural Equation Modeling (Warp-PLS). The result helps explain the antecedents causing normative community pressure of the brand community. The implication of this study is that communitfy setter should regularly identify and analyze rules or practices within the community that might be potential barrier for the members in building engagement with the community.